Pengelolaan Situs di Kawasan Kokas Kabupaten Fak-Fak - Bau Mene (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
There’s a large a mount of archaeological remains in Kokas region, such as rock painting, natural caves used as man the past for inhabit earthenware remains, and Kokas have a beautiful sight of nature, this region is very potential to make as a tourism area. In management activities cooperation between the government and the public who possess this culture heritage management this site must interesting of continous so can incoming benefit for this region.